Safekeeping Safe Doors Using Arm Cortex-A53 Microcontroller By Android - Tri Handayani; Tri Yuliati; Susilo (Jurnal Mantik, 2022)
Safeguarding the safe by adding a lock or layered security makes it take a thief a long time to break into a safe. In order to increase the security of the safe, that is by adding a key that is controlled by a microcontroller. The conclusion obtained from this research is that a solenoid that functions as an electric lock can increase the level of security on a safe door controlled by a Raspberry Pi 3 Model B through an Android smartphone by entering a password.